Polymyositis as an unexpected presentation of canine leishmaniasis - Resende, Lucilene Silva Ruiz [UNESP]; Faustino, Fabiana Garcia [UNESP]; Rahal, Sheila Canevese [UNESP] (Wiley, 2020)
We describe a rare case of a dog with visceral leishmaniasis and clinical, electromyographical and muscle biopsy diagnosis of polymyositis without parasites on muscle biopsy.
Keywords: leishmaniasis; muscle disorders; polymyositis